Evaluation of live duckweed, Wolffia globosa as an allochthonous feed for Labeo rohita fry during nursery rearing. (1st April 2019) - Pradhan, Amrita; Patel, Arun Bhai; Singh, Soibam Khogen
Abstract: A 40 days feeding trial with Labeo rohita (rohu) fry was conducted in six outdoor cemented tanks (5m × 4m × 1 m; 6–8 cm soil base) to establish the relative impact of on‐farm grown live Wolffia globosa (a duckweed with crude protein of 28.57%) and a formulated iso‐nitrogenous feed (crude protein 28.37%) on growth performance, survival, health and overall quality of fingerlings. The experimental tanks were dried, limed at 250 kg/ha, filled with ground water and subsequently applied with cow dung (soaked overnight) and mustard oil cake at 1, 000 kg/ha and 50 kg/ha respectively. The fry were stocked at 0.3 millions/ha in six prepared tanks, and fed live Wolffia (T1) and formulated feed (T2). Results of the study indicate better performance ( p <  0.05) of fry in terms of final mean weight (7.83 g), length (8.82 cm), daily growth index (6.51 g %/day) and survival (89.5%) than those fed on formulated feed. Furthermore, significantly improved ( p <  0.05) feed utilization parameters viz. apparent feed conversion ratio (AFCR), apparent protein conversion efficiency (APCE), apparent protein efficiency ratio (APER); haematological parameters viz. total erythrocyte count (TEC), total leucocyte count (TLC), packed cell volume (PCV), plasma glucose and protein of fry were also observed in T1 (live Wolffia ). Overall findings from this study hints towards the possible utilization of on‐farm grown live Wolffia as a suitable nutrient source for fry rearing of L. rohita .